Malaysia and ASEAN-5 e-commerce research: bibliometric analysis and sustainable development - Khoong, Tai Wai; Chong, Kok Fei; Ooi, Pey Theng; Kumara Adji Kusuma,; Khor, Siak Kim (Penerbit Universiti Kebangsaan Malaysia, 2025)
E-commerce has proven its contribution to the global growth both pre- and post-pandemic, particular in Malaysia and ASEAN-5 countries. E-commerce extends beyond the online shopping, and forms new transactions model. The understanding of e-commerce trends within ASEAN-5 countries is essential to characterize digital economy development that impact global trade, digital divide bridging, and contribute to sustainable development. Hence, the objective of this study is to conduct bibliometric analysis on the Scopus indexed documents between ASEAN-5 countries. This study analysis utilized VOSviewer software to examine the distribution of bibliometric maps. The data was acquired from the Scopus database, whereby data filtering pertaining with the e-commerce terms contained in the title, keyword, and abstract areas. The documents published between 2013 and 2022 were chosen to capture the latest circumstances. During the studied period, Indonesia has the highest documents and items. Within the period, ASEAN-5 showed an increase trend of publication. ASEAN-5 showed various of the top five keywords occurrences, however similarity in sales term. The dataset items are further categorized into clusters. ASEAN-5 demonstrated association of theories in the documents except Philippines. The majority of the countries utilized consumer behavior theories, except Singapore focus mathematics concept. Besides, the sustainable development term frequently occurred within ASEAN-5, particularly Malaysia and Thailand, but not in Philippines. In addition, e-government term plays key research for Thailand and Philippines. The study finding provides a valuable insight for future study in the ASEAN-5 countries e-commerce by identifying key terms, significant publications, and collaborative networks. Researchers can build on this finding to explore specific study areas, consists of theories adopted, sustainable development, and e-government.